If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -6 = 11 Reorder the terms: -6 + z = 11 Solving -6 + z = 11 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + z = 11 + 6 Combine like terms: -6 + 6 = 0 0 + z = 11 + 6 z = 11 + 6 Combine like terms: 11 + 6 = 17 z = 17 Simplifying z = 17
| 2-3x/1-x=8/x-1 | | 3-5x=67 | | ln(1+x^2)=1+2lnx | | 1/4x-3/8=5 | | 2x+4=136 | | a+2b+3c=25 | | y=2y-4/y | | x+6=112 | | 8(2a-b)-5(6b-5a)= | | z^2+4z-3=0 | | 4x+21=9x-9 | | 7y(y)-5y+6-15y(y)-5y+6= | | 9x+14y+20+8x-13y-18= | | x^2-2x-22.4=0 | | (3x^2+8x)(25x^2-5x-2)=0 | | 6x(x+6y+z)= | | z^2-4z-12= | | 25r^2+60rg+36g^2=0 | | -3(8x-3y+4)= | | 8x^2y-4xy^2+5xy=0 | | 12=5k-4 | | x^2-31x+300=0 | | 5x+35=95 | | y=.20x*8+35 | | (12)-(y)=15 | | (10x-6-3p)= | | 2v-10v-12=(v-3)(v-3) | | y=.2x*8+35 | | 9.5+27= | | [x+2]=5 | | 0.2(60)+0.5x=0.1(60+x) | | a^3-3a^2+2a+9=0 |